The Stojka family - Hajská, Markéta (Karolinum Press, 2025)
The book traces the history of a Romani family from the territory of today’s Slovakia across the 19th and 20th centuries. Working with a large body of diverse historical sources as well as with a wealth of ethnographic data, Markéta Hajská places the story of the Stojka family in two historical arenas: the history of Czechoslovakia, as an example of a newly-emerging Central European nation-state during a highly turbulent period of complex political changes, and the history of Roms in Central Europe as a heterogeneous ethnic group that has historically formed part of local multi-ethnic societies.